A Modular Multilevel Dual Buck Inverter With Adjustable Discontinuous Modulation - Dan Lyu; Yichao Sun; Carlos Alberto Teixeira; Zhendong Ji; Jianfeng Zhao; Qi Wang (IEEE Access, 2020)
Conventional single-cell dual buck inverters present high reliability, however they cannot be directly used in high voltage applications, because of the limited voltage rating of commercial switching devices. Therefore, a novel modular multilevel dual buck inverter (MMDBI), capable of processing voltage and power at higher levels, requiring a single dc input voltage, is proposed in this paper. Non-interleaved phase-shifted discontinuous modulation (NIPSDM) and interleaved phase-shifted discontinuous modulation (IPSDM) schemes are applied to the proposed inverter to reduce the current stress in the switching devices. Despite beneficial to the converter efficiency, the use of these discontinuous modulation approaches results in current zero-crossing distortion, which needs to be appropriately managed. In this work, theoretical values for the common-mode and differential-mode current ripples under NIPSDM and IPSDM modulation strategies are derived, and each switching operating mode is fully analyzed. From that, an adjustable current threshold value, which depends on the theoretical current ripple magnitude, is incorporated into the modulation strategy, producing a minimum switching overlap period between the two buck cells that eliminates the current zero-crossing distortion and produces a high-quality output current. Extensive simulation and experimental investigations are presented to demonstrate the feasibility and effectiveness of proposed topology and adjustable discontinuous modulation strategy.